Liposomal Microencapsulation of Rodent-repelling Agents onto Jute Burlaps: Assessment of Cytotoxicity and Rat Behavioral Test - Ahmed A. Nada, Ahmed G. Hassabo, Amina L. Mohamed, Marwa M. Mounier, Nabil Y. Abou Zeid (Journal of Applied Pharmaceutical Science, 2016)
In Egypt, the world’s biggest wheat importer, about 7 to 10 percent of stored grains are damaged because of poor conditions of storage. Rodent invasion is considered as one of the main reasons that caused wheat grain damage. With respect of food safety, this work aims to treat the grain burlaps (containers) to rodent repellent. The rodent repellent agents was extracted from natural local resources. For the rodent repellent effectiveness, wheat burlaps are treated with rodent repelling agents using eco-friendly components. There are prepared using camphor oil, mint oil, and capsaicinoids (extracted from hot red pepper) as local resources to develop low cost and high-performance final product. The plan of work relies on two main axes; first, the experimental part in which burlap was treated for rodent repellent; second, testing and characterizing the treated samples for cytotoxicity and animal behavior test. The treatment was taking place by conventional pad-dry-cure technique.
Keywords: Liposome,Microencapsulation,rodent repellent, Functional coatings, Jute burlaps.